Analisis Pengaruh Faktor Morbiditas, Tingkat Pengangguran Terbuka (TPT), dan Angka Partisipasi Murni (APM) Terhadap Indeks Pembangunan Manusia di Provinsi DKI Jakarta Periode 2017-2021 - Lala Atika Sari (Journal of Management and Social Sciences, 2022)
This study was compiled to find out the results of an analysis of the factors that influence the human development index in DKI Jakarta Province for the 2017-2021 period. The human development index explains how people can access development outcomes in terms of income, health, education, and so on. HDI is based on three basic dimensions which include: 1. Long and healthy life (a long and healthy life); 2. Knowledge; 3. Decent standard of living. The purpose of this study is to analyze the components of each dimension that underlies the human development index, such as the Morbidity factor which is an extension of the dimensions of longevity and healthy life, the Net Enrollment Rate (APM) factor which is an extension of the education dimension, and the open unemployment rate factor. which is an extension of the dimension of a decent standard of living. These three components are used as independent variables to analyze their influence on the human development index in the DKI Jakarta province for the 2017-2021 period. This study is also used to rank the components that have the most influence to those that have the least impact on the HDI for DKI Jakarta province for the 2017-2021 period. This study uses Eviews-10 with time series data sourced from the DKI Jakarta Central Statistics Agency (BPS) web for the period 2017-2021. The research method used is the VECM (Vector Error Correction Model) which functions as an approach to predict long-term and short-term relationships in one time series data to other time series data. The results of this study say that the TPT variable (open unemployment rate), Morbidity Rate, and Net Participation Rate (APM) only make a small contribution to the Human Development Index in districts/municipalities in the Province of Jakarta. In the analysis results of the f test and t partial test, only two variables namely TPT (open unemployment rate) and morbidity have an influence on HDI. Meanwhile, the APM variable (pure enrollment rate) has no effect on HDI.